Empty Nest Status, Marital Closeness, and Perceived Health: Testing Couples' Direct and Moderated Associations with an Actor–Partner Interdependence Model. (January 2022) - Tracy, Eunjin L.; Putney, Jennifer M.; Papp, Lauren M.
Building on previous examinations of marital outcomes in the empty nest phase that have been based on surveys of individuals (primarily wives), the current study examined the direct effect of no longer living with children in the home (vs. continuing to live with children) on husbands' and wives' ratings of marital closeness as well as their perceived health. The study also tested whether couples' empty nest status moderated the associations between spouses' marital closeness and health. Analyses were based on 3, 765 mixed-sex couples drawn from the Wisconsin Longitudinal Study. Dyadic multilevel modeling and actor–partner interdependence models were used to test hypotheses. Results indicated that, accounting for known covariates, being in the empty nest was directly linked with both husbands and wives reporting higher levels of marital closeness and with wives (only) reporting better health. Moderating findings were less consistent, with the single reliable moderation result indicating that wives' perceived health was improved at higher levels of their husbands' marital closeness only among couples who were still living with children in the home. Clinical implications and future research directions are discussed.